Keterkaitan Budaya Organisasi dengan Kinerja Karyawan: Analisis Literatur dalam Konteks Global dan Lokal - Nurbit, Nurbit; Rahmat, Hayatul Khairul; Rezkillah, Nafil; Veronika, Nina; Akbar, Rahmad; Habibullah, Abdi Naufal (PT Hakhara Akademia Indonesia, 2025)
This study examines the relationship between organizational culture and employee performance with a focus on global and local contexts. Through a literature review, it was found that organizational culture significantly influences employee performance, including aspects of motivation, commitment, and productivity. A culture that supports open communication, recognition of achievements, and effective leadership plays a crucial role in enhancing individual and team performance. However, this relationship is affected by cultural differences between collectivistic and individualistic societies. Additionally, factors such as leadership, reward systems, and internal communication mediate this relationship. The study identifies the mechanisms underlying the influence of organizational culture on employee performance and offers practical recommendations for multinational organizations to design strategies that align with local cultural contexts. The findings aim to provide deeper insights into how organizational culture can enhance employee performance across diverse cultural backgrounds.